УСЛОВИЯ ПОСТРОЕНИЯ БЕЗДАТЧИКОВЫХ ЭЛЕКТРОМЕХАНИЧЕСКИХ СИСТЕМ НА ОСНОВЕ БЕСКОНТАКТНЫХ ДВИГАТЕЛЕЙ С ПОСТОЯННЫМИ МАГНИТАМИ - Акинин, К.П. (Інститут електродинаміки НАН України, Київ, 2011)
Development features of sensorless electromechanical systems on the basis of permanent magnet brushless motors are considered. Example of pulse-width modulation algorithm for sensorless control are given. References 12, table 1, figures 2.